THE ROLE OF "CHILDREN'S ASSOCIATIVE DICTIONARY" IN THE DEVELOPMENT OF UZBEK LINGUISTICS (Spectrum Journal of Innovation, Reforms and Development, 2023)
In the article psycholinguistics development as a result surface came new type dictionary - «Children associative dictionary of «Uzbek linguistics in development scientific and practical importance in particular the word held. In it of the dictionary to himself special linguistic, lexicographic aspects about some considerations reported.